Peluang Dan Tantangan Manfaat Cash Waqf Linked Deposit Pada Sektor Hijau Dalam Hukum Linkungan Indonesia - Muhamad Afifullah; Irwan Triadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The presence of Cash Waqf Linked Deposit (CWLD) in 2023 which is used for education is a development point for productive waqf, where previously the government had issued Cash Waqf Linked Sukuk (CWLS) as a waqf instrument with various uses including in the sustainable development sector, as well as the encouragement for the Islamic financial industry in secreening financing to protect the environment. Because of this, a special study is needed regarding whether CWLD can be used for sustainable development according to Indonesian law. This scientific work is included in normative jurisprudence, so that in compiling descriptive analysis used with a literature study approach, utilising legal sources of legislation and other scientific works. The research results obtained, namely The opportunity to apply CWLD benefits to the sustainable sector is supported by a legal structure that has synergised to develop waqf. Regulations issued by agencies and the Islamic financial industry. The legal culture of gotong royong that has been rooted in society is an additional value in the development of waqf. However, the weakness lies in the absence of CWLD product development in the sustainable development sector and the absence of specific regulations governing CWLD. The next challenge is to maintain the synergy between stakeholders in the legal structure, formulate specific regulations related to CWLD, and increase the inclusion and literacy of Islamic finance through socialisation, so that the development of productive waqf and the Islamic finance industry can continue to increase.